Phosphorylatedα-Synuclein-Copper Complex Formation in the Pathogenesis of Parkinson’s Disease - Castillo González, Juan Antonio; Loera Arias, María de Jesús; Saucedo Cárdenas, Odila; Montes de Oca Luna, Roberto; García García, Aracely; Rodríguez Rocha, Humberto (2017)
Parkinson’sdiseaseisthesecondmostimportantneurodegenerativedisorderworldwide.ItischaracterizedbythepresenceofLewy bodies,whicharemainlycomposedof